2020
DOI: 10.1016/j.jarmac.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Directed forgetting affects how we remember and judge other people.

Abstract: The present study asks whether behaviors of another person can be intentionally forgotten, and whether forgetting affects how that person is evaluated. Participants read about negative and neutral behaviors of a fictional character and were then asked to forget or to keep remembering them. Afterwards, all participants learned of neutral behaviors associated with another character. After a short distractor or a 24-hour delay, implicit and explicit evaluations of both characters and memory for their behaviors we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Another relevant finding is that DF impairment can persist over significant delays (Abel & Bäuml, 2017;Scully & Hupbach, 2020), which is similar to the result of our Experiment 2. The long-term DF effect has important theoretical implications as it is inconsistent with the context change account and is not predicted by the inhibition account.…”
Section: Theoretical Implicationssupporting
confidence: 89%
“…Another relevant finding is that DF impairment can persist over significant delays (Abel & Bäuml, 2017;Scully & Hupbach, 2020), which is similar to the result of our Experiment 2. The long-term DF effect has important theoretical implications as it is inconsistent with the context change account and is not predicted by the inhibition account.…”
Section: Theoretical Implicationssupporting
confidence: 89%
“…For instance, Barnier et al (2007) demonstrated that people can intentionally forget autobiographical memories when these are generated by the participants in response to cue words and recalled together with the cue words at the time of testing. In addition, LMDF has been observed for product attributes ( Shapiro et al, 2006 ), simple actions ( Sahakyan and Foster, 2009 ), attitude statements ( Waldum and Sahakyan, 2012 ), line drawings ( Hupbach and Sahakyan, 2014 ), everyday objects ( Hupbach et al, 2018 ), and behavioral descriptions ( Scully and Hupbach, 2020 ). Thereby, the list 1 forgetting is typically eliminated when the items are related between lists (e.g., Conway et al, 2000 ; Barnier et al, 2007 ; Sahakyan and Goodmon, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…While there is evidence for functional independence (e.g., Carlston, 1980; Klein & Loftus, 1990), judgments can depend on behavior memory (Hastie & Park, 1986; Klein et al, 2002; Tormala & Petty, 2001). In a list-wise DF paradigm, we previously showed that explicit evaluations were related to behavior recall, and that both evaluations and recall were affected by DF instructions (Scully & Hupbach, 2020). In contrast to the present study, behaviors did not imply specific traits and participants explicitly evaluated actors on dimensions that were not directly linked to any presented behaviors.…”
Section: Discussionmentioning
confidence: 99%